Heat nonlinearity of surface waves at interface between finite gas pressure magnetized plasma and metal - Akimov, Yu.A.; Azarenkov, N.A.; Olefir, V.P. (Вопросы атомной науки и техники, 2003)
This report is devoted to the investigation of the non-linear mechanism of plasma electrons heating on dispersion properties of potential surface waves (SWs) that propagate along interface of metal-magnetized plasma of a finite pressure. The external steady magnetic field is perpendicular to the medium interface. The different mechanisms of electron energy losses in approach of a weak heating are considered. The spatial distribution of plasma electron temperature on the basis of energy balance equation in framework of the non-local electrons heating is obtained. The nonlinear shift of wavenumber and spatial attenuation coefficient at different plasma parameters are researched. The obtained results are valid both for semiconductor and gas plasma. Дана робота присвячена вивченню впливу нелінійного механізму нагріву електронів плазми на дисперсійні властивості потенціальних поверхневих хвиль (ПХ), що поширюються уздовж межі метал - магнітоактивна плазма кінцевого тиску. Зовнішнє стале магнітне поле спрямоване перпендикулярно межі розподілу середовищ. В наближенні слабкого нагріву розглянуто різні механізми втрати енергії електронів. Отримано просторовий розподіл температури плазми в рамках нелокального нагріву електронів на основі рівняння балансу енергії. Досліджено нелінійний зсув хвильового числа та нелінійний декремент просторового загасання ПХ в залежності від параметрів плазми. Отримані результати справедливі як для напівпровідникової, так і для газової плазми. Данная работа посвящена изучению влияния нелинейного механизма нагрева электронов плазмы на дисперсионные свойства потенциальных поверхностных волн (ПВ), распространяющихся вдоль границы металл - магнитоактивная плазма конечного давления. Внешнее постоянное магнитное поле направлено перпендикулярно границе раздела сред. В приближении слабого нагрева рассмотрены различные механизмы потери энергии электронов. Получено пространственное распределение температуры плазмы в рамках нелокального нагрева электронов на основе уравнения баланса энергии. Исследованы нелинейный сдвиг волнового числа и нелинейный декремент пространственного затухания ПВ в зависимости от параметров плазмы. Полученные результаты справедливы как для полупроводниковой, так и для газовой плазмы.